Den kirkelige anskuelse som svar til Karon: Randbemærkninger til tre sømandssange af Grundtvig - Schiøler, Aage (Grundtvig-studier, 2004)
Den kirkelige anskuelse som svar til Karon. Randbemærkninger til tre sømandssange af Grundtvig[Grundtvig’s Ecclesiology as an Answer to Charon: Marginal Notes on three “ Sailor’s Songs ” by N.F.S. Grundtvig]By Aage Schiøler The article is an attempt to place Grundtvig’s “ Lay of Departure” (Bortgangskvæde, text B. H. Begtrup’s title) in relation to his view on human life and Christianity, placing it also as part in the course of his authorship in order to describe more precisely the function within the poem’s context of the antique Greek myth about Charon and his boat, and to clarify the character of the poem as an answer to a situation of crucial existential impact. The method used is an analysis of the common motifs in the texts A, B, and C combined with a theological approach to the texts.The examination of the maritime motifs, especially the Sea and the Vessel, shows that when the sea relates explicitly to Biblical texts, as is the case in B, it depicts death as an active force, able to annihilate life totally if no divine interference takes place. The vessel sounds echoes of the traditional use of a ship as representation of the Church seen as a tool for the action of God against mortality and in favour of life. The vessels in A, B, and C, however, also bear reminiscences of Skidbladner, the ship of Frej, one of the Nordic gods, and Noah’s ark, of the Fayak vessel, that carried Odysseus to Ithaca, and, in the case of B, Charon’s barge - not to mention different actual vessels from Grundtvig’s lifetime. Therefore, it is the function of the vessel rather than its origin in literature and shipbuilding that demands the main attention. And this function is to bring man from the wellknown, actual form of life to a proclaimed condition of existence, which is brought into focus by the imminence of death, the poet’s and the reader’s.In order to specify the character of the answer to death in text B, the wording within the western tradition of this incident, especially Grundtvig’s own terminology, is sketched. He maintains the view that neither the language of common sense nor of philosophy of his day with its tendency to limitless analysis and speculation offers an answer to the question raised by death. The motifs expressing his own attempt to answer are found in all three texts, namely preaching vis-à-vis praise, Baptism and Communion, by Grundtvig himself called “the three main festivals”, the three lesser festivals being Christmas, Easter and Whitsun. In this context, the function of “ Sjale-Fargen” in text B is defined as being the vessel for the last lap of the same long and dangerous voyage of life, but now marked by its imminent end and the reduction of the dangers to one: Death. Thus this last lap might be seen as a new navigation, but the force carrying the vessel across the sea is one and the same.The concluding part of the article is a comparison between the notions and dynamics of the language Grundtvig uses when speaking of the Church, and the structure of text B, v. 3-5, the verses put in opposition to the situation described in B, v. 1-2. It includes a rough outline of Grundtvig’s understanding of “the World” and a short characteristic of his use of non-Biblical material in Christian statements. Finally, an attempt is made to state more precisely the validity of this “answer to Charon” in contemporary context.